Combined group and individual therapy for patients with avoidant personality disorder—A pilot study - Wilberg, Theresa; Pedersen, Geir; Bremer, Kjetil; Johansen, Merete Selsbakk; Kvarstein, Elfrida Hartveit (Frontiers in Psychiatry, 2023)
Objective: Avoidant personality disorder (AvPD) is a common disorder within mental health services, associated with significant psychosocial impairment. The disorder has been neglected in research. There are currently no evidence-based treatments for AvPD, and there is a need for treatment studies focusing particularly on this form of personality pathology. The present study was a pilot study of combined group and individual therapy for patients with AvPD, based on mentalization-based and metacognitive interpersonal therapy. The aim was to investigate the feasibility of the treatment program and the course of symptoms and personality functioning during treatment and one-year follow-up. Methods: The study included 28 patients. Clinical evaluation at baseline comprised structured diagnostic interviews and patients’ self-report of symptoms, psychosocial function, interpersonal problems, personality functioning, alexithymia, self-esteem, attachment style, therapeutic alliance, and client satisfaction. Patients’ self-report were repeated at the end of treatment and one-year follow-up. Results: The drop-out rate was 14%. Average treatment length among the 22 treatment completers was 17 months. Mean levels of therapeutic alliance and client satisfaction were satisfactory. Effect sizes were large for global symptom distress, depression, anxiety, and psychosocial adjustment, and in the moderate range for aspects of personality functioning. Yet, the results showed a wide range of outcomes among the patients. Conclusions: This pilot study shows promising results for combined group- and individual therapy for AvPD patients with moderate to severe impairment. Larger scale studies should be conducted to increase empirically based knowledge to guide development of differentiated treatments adapted to patients’ various levels of AvPD severity and profiles of personality dysfunction.